Bladder cancer therapy without toxicity-A dose-escalation study of alpha1-oleate - Hien, Tran Thi; Ambite, Ines; Butler, Daniel; Wan, Murphy Lam Yim; Tran, Tuan Hiep; Höglund, Urban; Babjuk, Marek; Svanborg, Catharina (International journal of cancer, 2020)
Potent chemotherapeutic agents are required to counteract the aggressive behavior of cancer cells and patients often experience severe side effects, due to tissue toxicity. Our study addresses if a better balance between efficacy and toxicity can be attained using the tumoricidal complex alpha1-oleate, formed by a synthetic, alpha-helical peptide comprising the N-terminal 39 amino acids of alpha-lactalbumin and the fatty acid oleic acid. Bladder cancer was established, by intravesical instillation of MB49 cells on day 0 and the treatment group received five instillations of alpha1-oleate (1.7-17 mM) on days 3 to 11. A dose-dependent reduction in tumor size, bladder size and bladder weight was recorded in the alpha1-oleate treated group, compared to sham-treated mice. Tumor markers Ki-67, Cyclin D1 and VEGF were inhibited in a dose-dependent manner, as was the expression of cancer-related genes. Remarkably, toxicity for healthy tissue was not detected in alpha1-oleate-treated, tumor-bearing mice or healthy mice or rabbits, challenged with increasing doses of the active complex. The results define a dose-dependent therapeutic effect of alpha1-oleate in a murine bladder cancer model.
Keywords: Toxicity Tests, Subchronic; nádorové buněčné linie; dose escalation; Drug Screening Assays, Antitumor; nádory močového měchýře; aplikace intravezikální; Disease Models, Animal; lack of toxicity; Alpha1-oleate; screeningové testy protinádorových léčiv; Urinary Bladder; Oleic Acid; Mice; Cell Line, Tumor; kyselina olejová; močový měchýř; Lactalbumin; Antineoplastic Agents; bladder cancer therapy; modely nemocí na zvířatech; ženské pohlaví; testy subchronické toxicity; protinádorové látky; zvířata; Humans; králíci; Rabbits; myši; Urinary Bladder Neoplasms; Administration, Intravesical; Female; laktalbumin; lidé; Animals